Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Certainly! Let's solve the problem step by step.
We are given two functions:
[tex]\[ h(x) = x^2 + 1 \][/tex]
[tex]\[ k(x) = x - 2 \][/tex]
We need to find [tex]\((h + k)(2)\)[/tex].
### Step 1: Calculate [tex]\(h(2)\)[/tex]
To find [tex]\(h(2)\)[/tex], substitute [tex]\(x = 2\)[/tex] into the function [tex]\(h(x)\)[/tex]:
[tex]\[ h(2) = 2^2 + 1 \][/tex]
[tex]\[ h(2) = 4 + 1 \][/tex]
[tex]\[ h(2) = 5 \][/tex]
### Step 2: Calculate [tex]\(k(2)\)[/tex]
Next, substitute [tex]\(x = 2\)[/tex] into the function [tex]\(k(x)\)[/tex]:
[tex]\[ k(2) = 2 - 2 \][/tex]
[tex]\[ k(2) = 0 \][/tex]
### Step 3: Calculate [tex]\((h + k)(2)\)[/tex]
The function [tex]\((h + k)(x)\)[/tex] is defined as the sum of [tex]\(h(x)\)[/tex] and [tex]\(k(x)\)[/tex]:
[tex]\[ (h + k)(x) = h(x) + k(x) \][/tex]
So, when [tex]\(x = 2\)[/tex]:
[tex]\[ (h + k)(2) = h(2) + k(2) \][/tex]
[tex]\[ (h + k)(2) = 5 + 0 \][/tex]
[tex]\[ (h + k)(2) = 5 \][/tex]
Therefore, the value of [tex]\((h + k)(2)\)[/tex] is [tex]\(\boxed{5}\)[/tex].
We are given two functions:
[tex]\[ h(x) = x^2 + 1 \][/tex]
[tex]\[ k(x) = x - 2 \][/tex]
We need to find [tex]\((h + k)(2)\)[/tex].
### Step 1: Calculate [tex]\(h(2)\)[/tex]
To find [tex]\(h(2)\)[/tex], substitute [tex]\(x = 2\)[/tex] into the function [tex]\(h(x)\)[/tex]:
[tex]\[ h(2) = 2^2 + 1 \][/tex]
[tex]\[ h(2) = 4 + 1 \][/tex]
[tex]\[ h(2) = 5 \][/tex]
### Step 2: Calculate [tex]\(k(2)\)[/tex]
Next, substitute [tex]\(x = 2\)[/tex] into the function [tex]\(k(x)\)[/tex]:
[tex]\[ k(2) = 2 - 2 \][/tex]
[tex]\[ k(2) = 0 \][/tex]
### Step 3: Calculate [tex]\((h + k)(2)\)[/tex]
The function [tex]\((h + k)(x)\)[/tex] is defined as the sum of [tex]\(h(x)\)[/tex] and [tex]\(k(x)\)[/tex]:
[tex]\[ (h + k)(x) = h(x) + k(x) \][/tex]
So, when [tex]\(x = 2\)[/tex]:
[tex]\[ (h + k)(2) = h(2) + k(2) \][/tex]
[tex]\[ (h + k)(2) = 5 + 0 \][/tex]
[tex]\[ (h + k)(2) = 5 \][/tex]
Therefore, the value of [tex]\((h + k)(2)\)[/tex] is [tex]\(\boxed{5}\)[/tex].
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.